Restenosis and Therapy - Laszlo Denes; Laszlo Entz; Veronika Jancsik (International Journal of Vascular Medicine)
The vascular disease involves imbalanced function of the blood vessels. Risk factors playing a role in development of impaired vessel functions will be briefly discussed. In ischemia/reperfusion (I/R), ischemic hypoxia is one of the cardinal risk factors of restenosis. Various insults are shown to initiate the phenotype switch of VSMCs. The pathological process, leading to activated inflammatory process, complement activation, and release of growth factors, initiate the proliferation of VSMCs in the media and cause luminal narrowing and impaired vascular function. The review summarizes the alteration process and demonstrates some of the clinical genetic background showing the role of complement and the genotypes of mannose-binding lectin (MBL2). Those could be useful markers of carotid restenosis after stent implantation. Gene therapy and therapeutic angiogenesis is proposed for therapy in restenosis. We suggest a drug candidate (iroxanadine), which ensures a noninvasive treatment by reverse regulation of the highly proliferating VSMCs and the disturbed function of ECs.